Study of replenishment process w.r.t. Supply Chain Management at Torrent Pharmaceuticals Limited - Chawla, Prakash M. (Gyan Management Journal, 2013)
In 2008, the domestic pharma market in India was expected to be US10.76 billion and this is likely to increase at 9.5 per cent,Jrom 2011 to 2015. This makes it 3"’ globally in terms of volume 8% of global total) and 14th in terms of value (less than 1 % of global total). The company has adopted anticipatory responsive business model in replenishment process. The Primary Channel process is to transfer finished products from mother warehouse (manufacn;ring to mother warehouse) to carrying &forwarding agent. Subsequendy, the Secondary Channel is catering by fulfilling customer order from carrying & forwarding agent to Stockiest (wholesaler) to retailers.